Theory of planned behavior–based nutrition education to enhance knowledge and fruit-vegetable consumption determinants among elementary school children in Bogor Regency - Zafira, Tsuraya; Dwiriani, Cesilia Meti; Khomsan, Ali (AcTion: Aceh Nutrition Journal, 2026)
Nutritional problems among school-age children remain significant, mainly due to unbalanced diets and low vegetable and fruit intake. In Indonesia, 97.7% of students do not meet the recommended consumption levels, with West Java reaching 98.3%. Most nutrition education programs emphasize knowledge improvement without considering the psychological factors influencing eating behavior. The Theory of Planned Behavior (TPB), which highlights the role of intention in shaping behavior, has rarely been applied in Indonesia. This study examined the effect of TPB-based nutrition education on knowledge, attitude, subjective norm, perceived behavioral control, and intention to consume vegetables and fruits among elementary students in Bogor District. Using a quasi-experimental design with multiple random sampling, 70 fifth-grade students were divided into treatment and control groups (n=35 each). The instruments showed good validity (r-count > r-table) and reliability (Cronbach’s alpha > 0.7). The results indicated significant improvements in all TPB constructs (p < 0.05), except for subjective norm in the control group, with higher Cohen’s d values in the treatment group. TPB-based nutrition education effectively enhanced students’ intentions and behaviors toward consuming fruits and vegetables. Further research should consider longer interventions, follow-up evaluations, and the inclusion of additional influencing factors.